Persistent Gastrointestinal Angiodysplasia in Heyde's Syndrome after Aortic Valve Replacement - Akutagawa, Takashi (Intern Med, 2017)
A 67-year-old woman with recurrent gastrointestinal bleeding and aortic valve stenosis presented with spurting bleeding from angiodysplasia of the upper jejunum. As electrophoresis revealed decreased levels of high-molecular-weight (HMW) von Willebrand factor (VWF) multimers, she was diagnosed with Heyde's syndrome. After aortic valve replacement, her HMW VWF levels quickly recovered to normal, and the gastrointestinal bleeding ceased. However, capsule endoscopy still revealed gastrointestinal angiodysplasia six months later. This case shows that minute analyses of VWF multimers enable the diagnosis and confirmation of the resolution of Heyde's syndrome, and implies that gastrointestinal angiodysplasia can be attributed to unknown factors other than decreased VWF multimers.